Microstructure and doping effect on the enhancement of the thermoelectric properties of Ni doped Dy filled CoSb3 skutterudites. Issue 12 (27th September 2018) - Trivedi, Vikrant; Battabyal, Manjusha; Balasubramanian, Priyadarshini; Muralikrishna, G. Mohan; Jain, Pawan Kumar; Gopalan, Raghavan
Abstract : The thermoelectric properties of nanostructured Ni doped Dy filled CoSb3 skutterudites (Dy0.4 Co4− x Ni x Sb12 ( x = 0, 0.4, and 0.8)) have been reported. Abstract : The thermoelectric properties of nanostructured Ni doped Dy filled CoSb3 skutterudites (Dy0.4 Co4− x Ni x Sb12 ( x = 0, 0.4, and 0.8)) have been reported. The samples are processed using a solid-state synthesis route. The structural analysis of the samples using X-ray diffraction reveals the existence of a single skutterudite phase in Ni doped samples irrespective of the Ni concentration. Microstructure studies using transmission electron microscopy and scanning electron microscopy show the existence of nanometer (∼60 nm) size equiaxed grains in the investigated samples. A few recrystallized elongated grains (∼200 nm) are observed in the Dy0.4 Co3.2 Ni0.8 Sb12 sample. The power factor of the Dy0.4 Co3.2 Ni0.8 Sb12 sample is enhanced to 5.2 mW mK −2, which is the highest power factor for the doped ternary skutterudites reported so far. The enhancement of the power factor is due to the substantial reduction in electrical resistivity with an increase in Ni concentration at higher temperature. The lattice thermal conductivity is drastically reduced to 0.3 W mK −1 at 773 K in the Dy0.4 Co3.2 Ni0.8 Sb12 sample due to the enhanced phonon scattering from Ni induced point defects and grain boundaries. As a result, a huge increase in the figure of merit ( ZT ∼ 1.4 ± 0.14) at 773 K is observed in the Dy0.4 Co3.2 Ni0.8 Sb12 sample, the highest among those of the single element filled CoSb3 skutterudites reported so far at this temperature. Hence, Ni doping could enhance the thermoelectric efficiency of Dy filled CoSb3 skutterudites. This can be taken as a reference to synthesize CoSb3 skutterudite thermoelectric materials having a higher figure of merit.